Analisis Framing pada Pemberitaan Pengaturan Pengeras Suara Masjid di Media Online Akurat.co - Muhammad Fatih; Muhamad Ibtissam Han; Wahab Nur Kadri (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2023)
The emergence of regulations governing the use of loudspeakers in mosques seems to have caused a lot of controversy, especially when there was a statement from the Chief Minister of Religion Yaqut Cholil Qoumas. This polemic certainly gets a lot of attention from various news media by way of reporting that is in accordance with the ideology and interests of the media. Every news text contained in print media, as well as online is the result of construction by framing the point of view of an event. This study aims to find out the construction of accurate.co news regarding the Minister of Religion's rules regarding loudspeakers in mosques. Which parts will be eliminated and highlighted by Akurat.co to convey the reality of the news that has been constructed. This study uses the constructivism paradigm with the Zhong Dang Pan and Gerald M. Kosicki model media framing analysis method. This framing analysis model is divided into four analysis structures, namely: syntactic structure, script structure, thematic structure, and rhetorical structure. This study found that there was news framing that led to the element of media Accuracy.co's partiality towards the Ministry of Religion's regulations regarding the rules for loudspeakers in mosques. The construction of reality in the news text carried out by the media accurate.co was carried out as an effort to direct public opinion that Yaqut Cholil Qoumas' statement as chief minister was not to compare the sound of the call to prayer and the sound of dogs barking, but as an example that loud noises can disrupt tolerance in social life.